Gambaran Perilaku Self Injury dan Risiko Bunuh Diri pada Mahasiswa - Rina Suprayanti Rina; Fathra Annis Nauli; Ganis Indriati (HEALTH CARE : JURNAL KESEHATAN, 2021)
Introduction: Self injury and the risk of suicide are maladaptive behaviors that can harm a person, this behavior usually occurs due to problems that cannot be solved in an adaptive way so that someone solves the problem with maladaptive behavior. This study aims to determine the description of self injury behavior and the risk of suicide in students. Methodology: This research is descriptive research. The sample in this research came from college students with a total of 392 people and were recruited by the quota random sampling method. The data collection method used a Self-harm Inventory (SHI) questionnaire and an Assessment of Suicidal Intention. Results: This research shows the majority of early adulthood respondent (86.7%), with the most female (77.3%), and the religion of the respondents is Moslem (92.1%). The descriptions of self injury behavior in students is that those who have ever been (31.9%) and those who have never were (68.1%), while the risk of suicide was as many as (26.8%) and never (73.2%). The results for self injury were in the mild (30.9%) and severe (1.0%) categories, while the risk of suicide was in the low (24.5%) and high (2.3%) categories. Conclution: The results for this research shows there’s a few students have ever done self injury with low category and there’s a few students have ever done suicide risk with low category. The researcher hopes the next researcher can do further research on the therapy that can minimalize self injury behavior and the risk of suicide.